Psychiatric emergency department visits during the coronavirus disease-2019 pandemic - Sun, HaiMing; Liu, HaiChun; Ma, ChunYan; Chen, Zheng; Wei, YanYan; Tang, XiaoChen; Xu, LiHua; Hu, YeGang; Xie, YuOu; Chen, Tao; Lu, Zheng; Wang, JiJun; et al. (Frontiers in Psychiatry, 2023)
Background: Previous research has demonstrated the negative impact of the coronavirus disease-2019 (COVID-19) pandemic on mental health. Aims: To examine changes in the Chinese psychiatric emergency department (PED) visits for mental health crisis occurred during the pandemic. Methods: Before and during the COVID-19 pandemic, PED visit counts from the largest psychiatric hospital in China between 2018 and 2020 were investigated. Electronic medical records of 2020 PED visits were extracted during the COVID-19 pandemic period and compared for the same period of 2018 and 2019.Results: Overall, PED visits per year increased from 1,767 in 2018 to 2210 (an increase of 25.1%) in 2019 and 2648 (an increase of 49.9%) in 2020. Compared with two years before the epidemic, during the COVID-19 pandemic, the proportion of PED visits among patients with stress disorders, sleep disorder and anxiety disorder increased significantly. In terms of the distribution of demographic characteristics, age shows a younger trend, while the gender difference is not significant.These findings suggest that PED care seeking increases during the COVID-19 pandemic, underscoring the need to integrate mental health services for patients with stress, sleep, anxiety, and obsessive compulsive disorders during public health crises.